MEMBANGUN TEAMWORK PERFORMANCE DARI CULTURE DIVERSITY MELALUI COMMUNICATION DI LINGKUNGAN KERJA - Wijaya, Lianna; Samuel, Sylvia; Anggiani, Sarfilianty (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021)DO - 10.24843/IPTA.2021.v09.i01.p21, 2021)
The culture diversity in the working environment of Holland America Cruise Line caused by the multicultural and multinational crews. The purpose of the research is to analyze the culture diversity, communication, teamwork performance on board the cruise ship as well as to analyze the communication as the mediator to link the culture diversity and the teamwork performance in working environment of Holland America Cruise Line. The research involved 110 cruise ship crews as specific respondents and using qualitative method with purposive sampling questionnaire method. The primary data is collected based on questionnaires and the interviews session with the respondents while the secondary data is obtained by literature study and from the previous researchs. The result of this research find that communication is the most important factor to link the culture diversity and teamwork performance in the working environment of Holland America Cruise Line and the cruise ship management is expected to be able to help the crews ship to understand the cross-cultural before working on board and while working on board the cruise ship so this will able to support smooth operation of the cruise ship.